"Fosforilasi Maltodekstrin dan Potensi Prebiotiknya" - WAHYUNDARI, AGNES WIDYA PUTRI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The existence of bound phosphate on starch caused indigestible starch that produced the resistant starch (RS). Naturally, phosphate is linked on canna tubers, plantain and potato. The low degree of substitution (DS) on the tubers produced low content and yield of RS. In order to increase the DS, it was done phosphorylation on starch resulted low DS, content and yield of RS. In this research phosphorylation was done on maltodextrin (MD) that produced phosphate maltodextrin (MDF) to increase the linked phosphate. The objectives of this research were to determine the time reaction and concentration of sodium tripolyphosphate (STPP) of phosphorylation to result optimum DS of MDF, to determine the effect of DS on content and yield RS, and to determine prebiotics index (IP) of RS MDF. Chemically phosphorylation MD with esterification which used STPP on pH 9 at room temperature. For preparation RS, MDF was enzimatically hydrolyzed by Î±-amylase and glucoamylase at certain condition. IP assays was done by inoculating fecal slurry in basal medium on fours kinds of treatment which contain 1% RS MD, 1% RS MDF DS 0.0499, 1% inulin , and control for 24 h at 37Â°C in anaerobic condition. IP score was determined based on the change of Bifidobacteria spp., Bacteroides spp., Lactobacilli, and Clostridium spp. population for 0 and 24 h growth unders same condition. The result of this research showed that the MD phosphorylation with STPP caused substituted phosphate on glucose unit. The highest DS on time reaction 30 min and 10% concentration of STPP is 0.0499. MDF DS 0.0499 produced the highest content and yield of RS that is 58.49 and 9.48%, while DS is higher than 0.0499 produced the lower content and yield of RS. The RS which produced from MD phosphorylation result higher IP score than unphosphorylation. IP score of RS MDF DS 0.0499 is 1.17 proven potential as a prebiotics.